Efektivitas Pemberian Murottal Al-Qur’an Surat Ar-Rahman dan Relaksasi Nafas Dalam Terhadap Kecemasan Pasien Sectio Caesarea G1P0AO - Nurdewi Putri Rizki Utami; Wulan Noviani; Eko Susanto (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Sectio caesarea (SC) is an important action to prevent the risk of death of the mother or baby during labor. However, the increasing number of operations raises concerns about the health and psychological impacts on mothers. Pre-operative anxiety is often experienced by CS patients and can have a negative impact on the labor process. This study used a case study with 1 intervention patient and 1 control patient. Nursing care is provided to G1P0AO pregnant women who experience anxiety before undergoing SC surgery. Intervention in the form of murottal of Al-Qur'an Surah Ar-Rahman and deep breathing relaxation was given for 45 minutes before the operation process. Scoring of reduced anxiety levels in intervention and control patients before and after therapy showed a significant effect. Patients who received the intervention experienced significant reductions in blood pressure and pulse, indicating decreased anxiety. In contrast, control patients had increased blood pressure and pulse, indicating increased anxiety. Conclusion: Murottal therapy of Al-Qur'an Surah Ar-Rahman and deep breathing relaxation significantly reduce anxiety levels in SC patients. Integration of these nonpharmacological therapies in clinical protocols may aid in the preoperative preparation of SC patients. Further research is needed to confirm these findings and explore their potential applications in other medical contexts.